2017
DOI: 10.20964/2017.07.44
|View full text |Cite
|
Sign up to set email alerts
|

Mercury(II) Trace Detection Using a Glassy Carbon Electrode Functionalized by Chemically Prepared Gold Nanoparticles. Influence of Coating Process on Surface Reactivity and Analytical Performances

Abstract: An electrochemical sensor dedicated to Hg(II) trace detection was elaborated based on a gold nanoparticles (AuNPs) modified glassy carbon (GC) electrode. AuNPs were prepared using the Turkevich method and deposited on GC by drop casting. Different protocols including suspension filtration and evaporation temperature control were tested and their influence both on coating morphology and electrochemical activity assessed. From structural characterization, it can be concluded that neither the filtration step nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…3). As presented in a previous study [24], star and pyramidal geometric arrangements were observed (Fig. 3a).…”
Section: Characterization Of the Functionalized Electrodesupporting
confidence: 83%
See 4 more Smart Citations
“…3). As presented in a previous study [24], star and pyramidal geometric arrangements were observed (Fig. 3a).…”
Section: Characterization Of the Functionalized Electrodesupporting
confidence: 83%
“…On the other hand, this peak decreased all along the scanning for each electrode, showing a decrease of the AuNPs active surface. This trend was already observed in several studies including one of our previous work with drop-casted AuNPs [24,55,56]. It is the consequence of a dissolution-redeposition mechanism of the AuNPs during the cycling in H 2 SO 4 : during the oxidation scan the smallest AuNPs dissolve in the solution and redeposited on the remaining AuNPs during the reduction scan, leading to NPs growth and to a subsequent decrease in active surface area.…”
Section: Interfacesupporting
confidence: 69%
See 3 more Smart Citations